EXPLORING THE RELATIONSHIP BETWEEN NUTRITION AND AUTOIMMUNE DISEASE OUTCOMES: A SYSTEMATIC REVIEW OF CURRENT EVIDENCE - Syafiyati, Wahyu (STIKES Syedza Saintika Padang, 2025)
Autoimmune diseases are a group of immune disorders characterized by immune system activity that attacks the body's own cells and tissues. Nutritional factors have been linked to immune system regulation and may contribute to the progression and management of autoimmune diseases. However, further studies are needed on the relationship between diet, micronutrient status and clinical outcomes of autoimmune patients. This study aims to explore the relationship between nutrition and autoimmune disease outcomes by reviewing the latest available scientific evidence. This study is a systematic literature review that examines the results of recent research on the role of nutrition in autoimmune diseases. Articles were selected based on relevance to the topic, valid research methods, and relevance to nutritional strategies that can be applied in autoimmune disease management. Nutrients have been shown to have a significant impact on immune system regulation and autoimmune disease progression. Vitamin D, omega-3, and zinc have immunomodulatory roles that can suppress inflammation and improve immune balance. Plant-based diets and anti-inflammatory diets are associated with improved symptoms and reduced autoimmune disease activity. In contrast, diets high in saturated fat and sugar increase inflammation and worsen autoimmune conditions. Evidence-based dietary interventions can be an effective strategy in improving clinical outcomes of autoimmune patients. However, individual responses to specific diets vary, so a more personalized approach to nutrition needs to be developed. Collaboration between medical personnel, nutritionists, and researchers is needed to develop more specific nutritional guidelines in the management of autoimmune diseases